Evaluation of Cooking Oil as Processing Addtive for Natural Rubber - Y. M. SYAMIN; S. AZEMI; K. DZARAINI (ASEAN Journal on Science and Technology for Development, 2017)
It was reported recently that high amount of aromatic ring  or number of polycyclic aromatic hydrocarbon compounds found in aromatic oil are carcinogenic. This paper discusses the work to evaluate the Malaysian cooking oil as an alternative option to be used as process oil since cooking oil is safe to use and non-toxic. The performance of cooking oil is compared againstaromatic and paraffinioils. The results showed that rubber compounds containing cooking oil produced almostsimilar cure characteristicsas those produced by aromatic and paraffinioils indicating that it did not interfere with the vulcanization reaction. The physical properties of the vulcanizates containing cooking oil were almostsimilar to those of vulcanizates containing aromatic and paraffinioils, except the rebound resilience. The vulcanizates containing cooking oil gave higher resilience than vulcanizates containing aromatic and paraffinioils. High resilience is one of the desired features for a low rolling resistance tyre. Cooking oil provided this extra advantage.